Competitive advantages of the organization as a guarantee of its high competitiveness - Оksana Koshchii (Економічний форум)
The article deals with the issue of ensuring the competitiveness and efficiency of the functioning of organizations on the market. It has been proven that the prerequisite for ensuring high competitiveness of an organization is its competitive advantages. It is substantiated that in order to ensure the competitive advantages of the organization, it is necessary to pay considerable attention to their management, including their formation, development, and successful use. Different types of competitive advantages of the organization are given. It is substantiated that in order to ensure high competitiveness of the organization in the market, it needs to possess numerous competitive advantages of a high rank. To maintain competitive advantages in the long term, organizations should constantly improve existing competitive advantages and create new ones. Sources of formation of competitive advantages of the organization can be external and internal. It is proven that nowadays a special role in the formation of competitive advantages of the organization is played by its ability to create a developed communication system, use the advantages of the international division of labor, take into account geopolitical factors and the ability to develop and use various innovations. The following approaches can be used to form and develop the organization's competitive advantages: a consumer-oriented approach; competitor-oriented approach; resource approach. It is substantiated that a creative approach should be used to form and develop competitive advantages of the organization. The article provides modern features of managing the competitive advantages of organizations: constant and systematic work in the field of formation and development of competitive advantages; constant search for new sources of competitive advantages; simultaneous use of low-rank and high-rank competitive advantages; higher availability of technological competitive advantages for organizations from developing countries; the formation and development of competitive advantages requires significant financial costs and requires the availability of unique human resources. It is substantiated that the formation and development of the organization's competitive advantages should be carried out in accordance with the following requirements: be based on the organization's ability to be original compared to its competitors; ensure the uniqueness of the trademark compared to competitors in the long term; satisfy specific needs of consumers, etc.